Prevalence and burden of health problems in male junior elite ice hockey players - a 44-week prospective cohort study - Nordstrøm, A.; Bahr, R.; Clarsen, B.; Talsnes, O. (British Journal of Sports Medicine, 2021)
Background Little is known about the burden of overuse injuries and illnesses in junior elite ice hockey.